PHYSICAL AND HEALTHCARE RISKS: PERCEPTION OF NURSES WORKING IN SPECIALIZED CARE SERVICES. - Vieira Alves, Matheus Thiago; Pereira Rezende, Marina; Bernardes da Silva, Andréa Mara; Marinho Machado, Ana Rita (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2017)
Objective: to investigate, from the perception of nurses, the agents that promote occupational risks through exposure to agents. Method: this is a descriptive, cross-sectional study with 34 nurses enrolled in specialized care services. The data were collected through a self-administered questionnaire. Data analysis was done in the Statiscal Package for Social Sciences Program version 20.0 to obtain a descriptive analysis of the data. Results: Regarding the use of PPE, procedure gloves were considered by 100% of respondents and 58.82% of them referred gloves as preventive measures to physical agents and 52.94% also emphasized the ear protector. Conclusion: the study demonstrates the vulnerability of nurses to occupational risks, especially physical risk. It is suggested the implementation of training on the adoption of biosafety measures.